LONG URETERIC STRICTURES MANAGED BY USING BUCCAL MUCOSAL GRAFTS (Indonesian Journal of Urology, 2023)
ABSTRACT Objective: This study aims to describe the reconstruction of long ureteric strictures using buccal mucosal patch grafts and to report the short term outcome. Material & Methods: We retrospectively looked at our hospital inpatient and outpatient records of all patients who underwent surgical treatment for benign ureteric strictures. Imaging records and films, histopathological reports were reanalysed. The short term outcomes were also noted. Results: During this 10 years’ study period 8 patients (six Males and two Females) underwent 10 buccal mucosal grafts procedures. The mean age of the patients was 36.25 years and the mean length of the stricture was 7.13.41 cm. There were intraoperative complications noted and none of the patients needed either intra or post-operative blood transfusions. Serum creatinine remained stable at 6 and 12 weeks after surgery. Radioisotope renograms done 12-16 weeks after surgery showed improvement in function on the affected sides in all patients with adequate drainage. Conclusions: Buccal mucosal patch grafting and omental wrapping is feasible, effective, less complicated and associated with good outcomes at short term follow-up. Keywords: Reconstruction, ureteric stricture, buccal mucosa.